2021
DOI: 10.1109/access.2021.3054755
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gated Recurrent Unit Network Based on SVM and Moth-Flame Optimization Algorithm for Behavior Decision-Making of Autonomous Vehicles

Abstract: The behavior decision-making algorithm plays an important role in ensuring the safe driving of autonomous vehicles. However, existing behavior decision-making methods lack the capability to cope with future motion uncertainty in traffic, because the historical state of vehicles are not considered. This paper proposes a novel driving behavior decision-making method EnMFO-ImGRU based on Gated Recurrent Unit (GRU) and Moth-Flame Optimization algorithm (MFO). Four improvements are proposed in EnMFO-ImGRU. First, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Since decision-making is an important part that links perception and trajectory planning and greatly determines the safety and efciency of autonomous driving, extensive research around this issue can be found in the literature. In general, the typical research method of autonomous driving decision-making can be mainly categorized into 4 classes: rule-based [3][4][5], classical machine learning-based [6][7][8], deep reinforcement learning-based [9][10][11][12], and deep imitation learning-based [13][14][15]. Among many research methods, deep reinforcement learning has received great attention in recent years because it does not need a lot of human labeled training data, the learning style is closer to human learning, and the generalization ability is strong.…”
Section: Introductionmentioning
confidence: 99%
“…Since decision-making is an important part that links perception and trajectory planning and greatly determines the safety and efciency of autonomous driving, extensive research around this issue can be found in the literature. In general, the typical research method of autonomous driving decision-making can be mainly categorized into 4 classes: rule-based [3][4][5], classical machine learning-based [6][7][8], deep reinforcement learning-based [9][10][11][12], and deep imitation learning-based [13][14][15]. Among many research methods, deep reinforcement learning has received great attention in recent years because it does not need a lot of human labeled training data, the learning style is closer to human learning, and the generalization ability is strong.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a significant portion of related studies have been formulated using video-based trajectory datasets. These studies include driver behavior analysis ( 13 ), autonomous vehicle virtual testing ( 46 ), crash mitigation and avoidance system design ( 710 ), advanced autonomous control algorithm development ( 1114 ), surrogate safety measures ( 1518 ), among other safety applications. In the autonomous vehicle safety field particularly, datasets can provide training/testing samples for personalized algorithms of trajectory/intention prediction and vehicle control, given that the dataset contains rich information about driving preferences.…”
mentioning
confidence: 99%